THE EFFECT OF STORAGE ON PHYSICAL, CHEMICAL AND MICROBIOLOGICAL CHARACTERISTICS OF FISH WASTE ACIDIFIED USING FERMENTED VEGETABLES WASTE EXTRACT - Sulistiyanto, B.; Nugroho, K. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
Fish waste (“ikan rucah”) is part of discarded fishing product, which is composed by non-foodcategorized fish (NFC-fish). Quality of NFC-fish meal that was made by dipping in extract of fermentedvegetable’s waste has been reported better than commercial fish meal, but the effect after storingremained in question. Experiment was conducted to study the effect of different time of storing onphysic-organoleptical, chemical and microbiological characteristics of the acidified NFC-fish meal thatwas made by dipped in extract of fermented vegetable’s waste (FVW-exctract). The NFC-Fish wassoaked in the FVW-exctract by the ratio 1:1 (w/v) for 4 hours, and then it was dripped out and dried. Thedried fish was ground passed through 20 mesh, kept into plastic bags and stored at the room temperature(23-25 °C and 70-80% RH) for 0, 1, 2 and 4 months. Physic-organoleptical, chemical and biologycalcharacteristics were parameters observed. Experiment was conducted by completely randomized design(CRD). Data were analysed by the GLM of SAS. Actual number of moisture, crude protein, extractether, and proteolytic bacteria of fish meal were significantly influenced by time of storing (P<0.05).Dipping NFC-fish in the FVW-exctract effectively maintain the physical characteristics, pH, moisture,crude protein, extract ether and the number of proteolytic bacteria of fish meal up to 2 months ofstorage. Dipping NFC-fish in the FVW-exctract provide better characteristics on physical, chemical andmicrobiologycal than the commercial fish meal at the same condition of storage.